Early intervention in psychosis: a feasibility study financed by the Italian Center on Control of Maladies. Issue 2 (28th March 2014) - Cocchi, Angelo; Balbi, Andrea; Corlito, Giuseppe; Ditta, Guido; Di Munzio, Walter; Nicotera, Mario; Meneghelli, Anna; Pisano, Alessia; Preti, Antonio
Abstract: Aim: In November 2005 the Italian Center on Control of Maladies, a department operating under the Ministry of Health, financed a project aimed at evaluating the feasibility of a protocol of intervention based on the early intervention in psychosis (EIP) model within the Italian public mental health‐care network. Methods: The study was carried out between March 2007 and December 2009. It involved five centres operating under the Departments of Mental Health of Milan (Programma 2000), Rome (area D), Grosseto, Salerno (Nocera) and Catanzaro (Soverato). Results: Enrolment lasted 12 months, at the end of which 43 patients were enrolled as first‐episode psychosis (FEP), and 24 subjects as ultra high‐risk (UHR) patients. Both FEP and UHR samples included a preponderance of male patients. A family history of psychosis was rarely reported in both samples. The FEP incidence rate was lower than expected on the basis of international estimates of the incidence of schizophrenia but within the expected figure for the estimated Italian rates in three centres out of five. Conclusions: Overall, the study proved that an EIP centre can be established within the public Department of Mental Health to reach a good fraction of the cases in need of treatment. Since then, several studies have been set up to assess the feasibility of EIP in the Italian public mental health sector in Lombardy and Tuscany, and in 2012 the Emilia‐Romagna Regional Authority started an educational plan aimed at implementing the EIP model in all the Mental Health Departments in the region.